Prophylactic central neck dissection for cN0 papillary thyroid carcinoma: is there any difference between western countries and China? A systematic review and meta-analysis - Yang, Jiaxin; Han, Yuling; Min, Yu; Chen, Cheng; Chen, Jialin; Xiang, Ke; Liao, Jiahu; Feng, Yang; Hu, Daixing; Yin, Guobing (Frontiers in Endocrinology, 2023)
Background: Recommendations for the performance of prophylactic central neck dissection (pCND) in patients with clinically node-uninvolved (cN0) papillary thyroid carcinoma (PTC) are not the same. This meta-analysis set out to compare the effectiveness of pCND with total thyroidectomy (TT) in different countries and regions, mainly between western countries and China.Methods: The electronic databases PubMed, EMBASE, and Cochrane Library were searched for studies published until August 2022. The incidence rate of cervical lymph node metastases (LNM), locoregional recurrences (LRR) and postoperative complications were pooled by a random-effect model. Subgroup analyses based on different countries and regions were performed.Results: 18 studies involving 5,346 patients were analyzed. In the subgroup of western countries, patients undergoing pCND with TT had significantly lower LRR rate (69/1804, 3.82% vs. 139/2541, 5.47%; OR=0.56; 95% CI 0.37-0.85) and higher rate of temporary hypoparathyroidism (316/1279, 24.71% vs. 194/1467, 13.22%; OR=2.23; 95% CI 1.61-3.08) than that of TT alone group, while no statistically significant difference was found in the rate of permanent hypoparathyroidism (HPT), temporary and permanent recurrent laryngeal nerve (RLN) injury. In the Chinese subgroup, pCND with TT group had significantly higher incidence rate of both temporary HPT (87/374, 23.26% vs. 36/324, 11.11%; OR=2.24; 95% CI 1.32-3.81) and permanent HPT (21/374, 5.61% vs. 4/324, 1.23%; OR=3.58; 95% CI=1.24-10.37) than that of TT alone group, while no significant difference was detected in the rate of LRR, temporary and permanent RLN injury.Conclusion: Compared with the TT alone for cN0 PTC patients, pCND with TT had significantly lower LRR rate while higher temporary HPT rate in Europe, America and Australia, however, it showed no significant difference in decreasing LRR rate while significantly raised the rate of temporary and permanent HPT in China. More population-based results are required to advocate precision medicine in PTC.